2020
DOI: 10.1371/journal.pone.0231490
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver acceptability of the guidelines for managing young infants with possible serious bacterial infections (PSBI) in primary care facilities in rural Bangladesh

Abstract: IntroductionMany infants with possible serious bacterial infections (PSBI) do not receive inpatient treatment because hospital care may not be affordable, accessible, or acceptable for families. In 2015, WHO issued guidelines for managing PSBI in young infants (0-59 days) with simpler antibiotic regimens when hospital care is not feasible. Bangladesh adopted WHO's guidelines for implementation in outpatient primary health centers. We report results of an implementation research study that assessed caregiver ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 47 publications
11
31
0
Order By: Relevance
“…We had reasonable treatment coverage of approximately 60% in our study. Similar implementation research studies on PSBI in young infants from African and Asian countries reported variable treatment coverages of 16.3% in Sylhet and Chittagong in Bangladesh [24], 50% in Ethiopia [25], 42% in Kushtia district, Bangladesh [26], 63.8% in Malawi [27] and 95% in Nigeria [28]. Thus, except for the Nigeria study, our coverage proportions were comparable with other reported coverages.…”
Section: Discussionsupporting
confidence: 87%
“…We had reasonable treatment coverage of approximately 60% in our study. Similar implementation research studies on PSBI in young infants from African and Asian countries reported variable treatment coverages of 16.3% in Sylhet and Chittagong in Bangladesh [24], 50% in Ethiopia [25], 42% in Kushtia district, Bangladesh [26], 63.8% in Malawi [27] and 95% in Nigeria [28]. Thus, except for the Nigeria study, our coverage proportions were comparable with other reported coverages.…”
Section: Discussionsupporting
confidence: 87%
“…Efforts to implement WHO's PSBI guidelines and other newborn-focused interventions in low-resource settings should integrate local understanding of disease causations to increase demand for SYIs services from health facilities. Recent evidence on the feasibility of implementing PSBI guidelines in low-income countries have demonstrated the need for social and behavior change interventions targeting families and communities to improve careseeking from health facilities [36,37]. Strengthening community health structures by involving community health volunteers in creating awareness on the causes of illnesses and early identification in the community and referral of SYIs cases can be effective in improving community knowledge on the causes of illness in SYIs and improving care-seeking from…”
Section: Discussionmentioning
confidence: 99%
“…• Sub-activity 1.3: Ten postnatal home visits were to be made on days 1,3,7,14,21,28,35,42, 49 and 60 to promote optimal care practices such as breastfeeding, keeping the baby warm and hygiene; to identify danger signs in mothers and newborns, and to promote appropriate care-seeking.…”
Section: Intervention 10: Home-based Care Included 3 Sub-activitiesmentioning
confidence: 99%
“…Outpatient or community treatment is not only beneficial in terms of reduced costs but is also less disruptive for families and carries less risk of hospital-acquired infections [23]. The reasons for refusal to accept a referral to a hospital include lack of permission from concerned family members, lack of child care, religious and cultural beliefs, distance, cost of travel and treatment, concerns around quality of care and attitudes of health workers [7,[11][12][13].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation